Assessment of Prescribing Practice for Caesarean Section : Adherence to the Indonesian National Formulary - Nurmainah, Nurmainah; Arfida, Khaizurani; Ulfah, Ridha (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2026)
Background: The increasing prevalence of Caesarean Section (SC) deliveries and non-compliance with the National Formulary can lead to financial burdens for hospitals due to claim failures and higher drug costs. Understanding this relationship is crucial for improving cost efficiency and ensuring sustainable healthcare financing.Objectives: This study aims to analyse the percentage of prescribing compliance with the National Formulary and its impact on pharmacotherapy costs and the real costs of SC treatment at RSUD Dr. Soedarso.Methods: This research is an observational study with a cross-sectional design. Used medical record data of mild severity SC patients for the period January-December 2023. The sample consisted of 472 patients selected by purposive sampling. Descriptive Analysis and Spearman correlation were used to evaluate the relationship between prescribing compliance, pharmacotherapy cost, and real cost.Results: Adherence to the national formulary (97.10%). Spearman’s correlation analysis shows a significant negative correlation between adherence and pharmacotherapy costs. However, adherence has no significant correlation with total treatment costs, suggesting that factors like length of stay play a greater role.Conclusion: A significant negative correlation exists between compliance and pharmacotherapy cost, but no significant correlation with real costs. Future research should explore the relationship between total treatment costs and Length of Stay (LOS).